An iterative algorithm for optimal mould design in high-precision compression moulding - Sellier, M; Breitbach, C; Loch, H; Siedow, N (Proceedings of the Institution of Mechanical Engineers. Part B, Journal of engineering manufacture, 2007)
Abstract The mould design for the manufacturing of high-precision glass parts remains a challenging task. This motivates the present study which proposes an optimization technique to identify the mould design that yields the desired glass piece profile at the end of the compression moulding process with an accuracy of the order of 1 μm. The intuitive, yet very efficient method consists in computing at each optimization loop the mismatch between the deformed and desired glass piece geometries and using this information to update the mould design. The deformed glass piece geometry is computed using the commercial finite element package ABAQUS. This package is well suited to model the multistage forming process, the complex rheology of the glass, and the varying mechanical contact between the parts involved. The feasibility of the method is demonstrated in theory by designing the required mould for a convex-concave lens, where an accuracy of the order of 1 μm is achieved.